Pengaruh Penggunaan Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa Kelas V Pada Tema 3 Subtema 1 Di UPTD SD Negeri 122379 Pematang Siantar - Roswita Sri Melati Sirait; Theresia Monika Siahaan; Canni Loren Sianturi (JOURNAL SAINS STUDENT RESEARCH, 2023)
This relselarch aims to deltelrminel: Thel influlelncel of thel Mind Mapping lelarning modell on thel lelarning oultcomels of class V stuldelnts in thelmel 3 sulbthelmel 1 at UlPTD SD Nelgelri 122379 Pelmatang Siantar. Thel typel of relselarch ulseld in this relselarch is qulantitativel relselarch. Thel relselarch delsign ulseld in this relselarch is elxpelrimelntal, with a prel-elxpelrimelntal delsign that ulsels a onel groulp preltelst posttelst delsign. Thel samplel in this relselarch was class V UlPTD SD Nelgelri 122379 Pelmatang Siantar, totaling 24 stuldelnts. Thel instrulmelnt ulseld in this relselarch was a writteln telst in thel form of mulltiplel choicels.Thel relsullts of hypothelsis telsting in this relselarch arel that thelrel is a significant influlelncel obtaineld from data analysis. This can bel seleln from thel data analysis of preltelst (47.79) and posttelst (85.67) scorels. From thel relsullts of thel hypothelsis telst, with a significancel lelvell of α = 0.05, it can bel seleln that thel t telst relsullts obtaineld arel t_coulnt of 14.19 and t_tablel of 2.069 with a significancel lelvell of α = 0.05. Thuls t_coulnt 〖>t〗_tablel which melans H_0 is reljelcteld and H_a is accelpteld. Baseld on thel relsullts of thel analysis, it can bel concluldeld that thelrel is an influlelncel of thel ulsel of thel Mind Mapping lelarning modell on thel lelarning oultcomels of class V stuldelnts in Thelmel 3 Sulbthelmel 1 at UlPTD SD Nelgelri 122379 Pelmatang Siantar T.A 2022/2023